The Johns Hopkins Fall Risk Assessment Tool: A Study of Reliability and Validity. Issue 1 (January 2018) - Poe, Stephanie S.; Dawson, Patricia B.; Cvach, Maria; Burnett, Margaret; Kumble, Sowmya; Lewis, Maureen; Thompson, Carol B.; Hill, Elizabeth E.
Abstract : Patient falls and fall-related injury remain a safety concern. The Johns Hopkins Fall Risk Assessment Tool (JHFRAT) was developed to facilitate early detection of risk for anticipated physiologic falls in adult inpatients. Psychometric properties in acute care settings have not yet been fully established; this study sought to fill that gap. Results indicate that the JHFRAT is reliable, with high sensitivity and negative predictive validity. Specificity and positive predictive validity were lower than expected. Abstract : Supplemental Digital Content is Available in the Text.